Respiratory Tract Infection: A Risk Factor for the Onset and Relapse of Adult-Onset Minimal Change Disease in Southern China. (28th August 2018) - Han, Huanqin; Wang, Shujun; Liang, Yanting; Lin, Jieping; Shi, Lei; Ye, Lin; Song, Shiting; He, Minjun; Li, Shihao; Chen, Futong; Pan, Qingjun; Liu, Hua-feng
Abstract : Aims/Introduction . Steroid resistance and frequent relapse are problems in the treatment of minimal change disease (MCD). However, epidemiological factors that influence steroid-resistant and relapse of MCD are rarely reported. This study evaluated potential factors that influence the onset and relapse of MCD and the epidemiological features of southern Chinese patients with adult-onset MCD. Patients and Methods . Patients with adult-onset MCD were included from the Affiliated Hospital of Guangdong Medical University, which is located in the southernmost part of China's mainland, between 2015 and 2016. Potential influencing factors were investigated. Results . Eighty-seven patients with incipient MCD were enrolled, and 85 of these patients were followed up; 71.8% (61/85) were steroid-sensitive and 28.2% (24/85) were steroid-resistant. In terms of seasonal distribution, the highest rate of incipient cases was in spring (39.1%, 34/87), which also showed a high rate of relapse cases (29.7%, 22/74). Among patients who were followed up for more than half a year and whose proteinuria completely resolved (69.4%, 59/85), 52.5% (31/59) were without relapse and 47.5% (28/59) were with relapse. Patients without relapse were older than those with relapse ( P <0.05). Before disease onset, 20.7% (18/87) of patients with incipient MCD were diagnosed with infection, including 94.5% (17/18) with respiratory tract infection. Fourteen patients in complete remission posttreatment developed an infection before relapse, including 85.7% (12/14) with respiratory tract infection. Conclusion . Steroid resistance and frequent relapse are current challenges for the treatment of adult-onset MCD in southern China, and respiratory tract infection may be a risk factor for onset and relapse. Additionally, younger patients with MCD tend to have more frequent relapse.